Financial Restructuring and Reform In Post-WTO China - Financial Restructuring and Reform In Post-WTO China (Kluwer Law International, 2007)
This book addresses the on-going process of financial restructuring and reform in post-WTO China from a legal perspective. Chapter 1 provides an overview of the impact of the WTO on China?s financial markets and financial law systems. Chapter 2 discusses reform of banking law and regulation in post-WTO China. Chapter 3 addresses the role of the central bank in China?s financial system, focusing on issues of independence and accountability of the People?s Banking of China (PBOC), China?s central bank. Chapter 4 analyses China?s compliance with WTO obligations in the area of banking. Chapter 5 discusses the role of asset management companies (AMCs) in China?s on-going banking restructuring and liberalization. Chapter 6 analyses the development of securities markets in China, the challenges being faced and the impact of the WTO. Chapter 7 describes insurance and its development in China, focusing on the role of the WTO in liberalization.